Legalitas dan Keabsahan Perkawinan Virtual dalam Perspektif Hukum Islam dan Hukum Positif Indonesia - Nurim Samual; Nur Kifaya Mutiara Sakina Hamzah; Ujang Abdul Fatah (Lembaga Pengembangan Kinerja Dosen, 2025)
The development of information and communication technology has transformed many aspects of social life, including the conduct of marriage. One notable change is the emergence of virtual marriage practices using electronic media such as video conferencing or online communication applications. This practice has triggered debate over whether it is valid under Islamic law and Indonesian positive law. This study aims to examine whether virtual marriage is valid under Islamic law and to investigate its legal validity based on the prevailing legislation in Indonesia. The study employs a normative legal approach by reviewing relevant legal regulations, examining key related concepts, and comparing different legal systems. The information sources cover various legal norms, comprising primary, secondary, and tertiary legal materials, analyzed through a qualitative approach. The findings show that within Islamic law, scholars hold differing opinions on the validity of a virtually conducted marriage contract (akad nikah). Some scholars permit such marriages as long as the pillars and conditions are fulfilled, while others reject them because the requirement of ittihad al-majlis (unity of assembly) has not been met. Under Indonesian law, virtual marriage is not yet explicitly regulated, but it may be considered valid if it fulfills the conditions set out in marriage regulations and can guarantee legal certainty for both parties. Therefore, clearer regulations are needed to accommodate technological developments in the marriage process while still upholding the principles of Islamic law and state law.